Impact of conventional sterilization and ohmic heating on the amino acid profile in vegetable baby foods. (April 2016) - Mesías, Marta; Wagner, Magali; George, Stéphane; Morales, Francisco J.
Abstract: Loss of nutrients during processing of baby foods should be minimized to maintain the nutritional quality and therefore to support a satisfactory nutritional status in infants. The present study aimed to evaluate the advantages of the ohmic heating versus conventional retort sterilization on the maintenance of the amino acid content and protein quality of sterilized vegetable baby foods. Results revealed that total protein content was not affected after both sterilization methods. However, after retort sterilization the content of total essential and non-essential amino acids significantly decreased in 35% and 9%, respectively, thus decreasing the quality protein. Contrarily, ohmic heating did not have effect on the total amino acid content and, therefore, this alternative process did not modify the protein quality of the sample. In conclusion, ohmic treatment may be successfully applied as an alternative method to conventional sterilization to maintain the nutritional quality of protein in vegetable baby foods. Industrial relevance: Ohmic heating is an emerging technology which applies an electric current to the food, promoting uniform and rapid heating in the product. This fact facilitates the destruction of microorganisms in a shorter period of time and reduces the possible losses of labile nutrients caused with the conventional thermal treatments such as pasteurization or sterilization. The purpose of the present study was to evaluate the effect of conventional retort sterilization and alternative sterilization by ohmic heating on the amino acid content and protein quality of vegetable baby foods. These findings could be used for the baby food industries in order to improve nutritional quality of these products after heating processes. Highlights: Amino acid content of unsterilized and sterilized vegetable baby foods was studied. Effects of retort sterilization and ohmic heating were compared. Total protein content was not affected by sterilization treatments. Retort treatment decreased both total essential and non-essential amino acid content. Ohmic heating did not affect both amino acid content and protein quality.